Ocean acidification does not impact shell growth or repair of the Antarctic brachiopod Liothyrella uva (Broderip, 1833) - Cross, Emma L.; Peck, Lloyd S.; Harper, Elizabeth M. (Journal of Experimental Marine Biology and Ecology, 2015)
Marine calcifiers are amongst the most vulnerable organisms to ocean acidification due to reduction in the availability of carbonate ions for skeletal/shell deposition. However, there are limited long-term studies on the possible impacts of increased pCO2 on these taxa. A 7month CO2 perturbation experiment was performed on one of the most calcium carbonate dependent species, the Antarctic brachiopod Liothyrella uva, which inhabits the Southern Ocean where carbonate ion saturation levels are amongst the lowest on Earth. The effects of the predicted environmental conditions in 2050 and 2100 on the growth rate and ability to repair shell in L. uva were tested with four treatments; a low temperature control (0°C, pH7.98), a pH control (2°C, pH8.05), mid-century scenario (2°C, pH7.75) and end-century scenario (2°C, pH7.54). Environmental change impacts on shell repair are rarely studied, but here repair was not affected by either acidified conditions or temperature. Growth rate was also not impacted by low pH. Elevated temperature did, however, increase growth rates. The ability of L. uva to continue, and even increase shell production in warmer and acidified seawater suggests that this species can acclimate to these combined stressors and generate suitable conditions for shell growth at the site of calcification.
Keywords: CO; Calcification; Carbonate saturation; Climate change; dept.egm; pH